Engineering functionally-optimized aptamers against SARS-Cov-2 for blocking spike-ACE2 interaction and aptasensor detection - Xiangdong Lai; Weiwei Zhao; Lihua Jiang; Jing Li; Muhammad Faizan Munawer; Jiejuan Lai; Jesus Alejandro Martinez Juarez; Miraj Ud din; Xiaoyang Zhang; Zhongquan Song; Tao Wu; Yiyue Ge; et al. (Materials Today Bio)
Both the limited research about structure-function relationship and the ill-defined process of conformational dynamic change greatly impede the development of aptamer engineering transformation and seriously restrict the practical applications of aptamers. In this work, an optimization strategy combining exonuclease III (Exo III) digestion and in silico simulation was presented for the first time for constructing high-affinity and functional aptamers and clarifying the three-dimensional (3D) structure of aptamer-target complexes and the conformational dynamic conversion in the process of aptamer recognizing its target. As a demonstration, the parent aptamer (Apt2) against SARS-CoV-2 spike subunit 1 (S1) was mutated or truncated at the predicted binding sites to produce eight derivatives (Seq1–Seq8). The progeny Seq3 exhibited a higher affinity for S1 and a better blocking effect on S1-angiotensin-converting enzyme 2 (ACE2) interaction compared to Apt2. Subsequently, Seq3 sealed the pores of nickel-doped zeolitic imidazolate framework-8 (NZIF-8) loaded with Rhodanine (Rho) to fabricate the aptasensor (NZIF-8-Rho-Apt) for inactivated virus detection, showing excellent performances in spiked actual samples. Therefore, this post systematic evolution of ligands by exponential enrichment (post-SELEX) is a very effective and general strategy for acquiring functionally-optimized aptamers.